2005
DOI: 10.1108/00214660580001171
|View full text |Cite
|
Sign up to set email alerts
|

Research on USDA farm credit programs: past, present, and future

Abstract: Federal farm credit programs currently administered by the USDA were initiated in the early 1900s to help the farm sector cope with natural disasters, and these programs have continued to evolve. There has been a rich history of research analyzing USDA farm credit programs and the effects they have had on farmers, ranchers, and credit markets. This paper highlights past research and offers a view of the future direction of research on federal farm credit programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In an attempt to justify the importance of farm credits, Ahrendsen et al (2005) noted that the Federal farm credit programmes currently administered by the United State Department of Agriculture [USDA] were initiated to help the farm sector cope with natural disasters. In a similar vein, Ellinger et al (2005) observed that the performance, management and risk exposure of financial institutions operating in rural and agricultural markets determine the cost of agriculture's access to financial capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an attempt to justify the importance of farm credits, Ahrendsen et al (2005) noted that the Federal farm credit programmes currently administered by the United State Department of Agriculture [USDA] were initiated to help the farm sector cope with natural disasters. In a similar vein, Ellinger et al (2005) observed that the performance, management and risk exposure of financial institutions operating in rural and agricultural markets determine the cost of agriculture's access to financial capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…that create obstacles for underserved, but deserving, borrowers in the farm sector to obtain the needed loan funds (Ahrendsen et al, 2005). Intense competition in the lending industry has compelled regular, commercial lenders to develop high credit risk assessment and loan approval standards that are quite difficult for certain farm borrowers to meet.…”
mentioning
confidence: 99%
“…Thus, the FSA accommodates such excluded or rejected clients, which are usually small and beginning farmers with inadequate business track record, among others, but have the potentials to thrive in the farming business (Dodson and Koenig, 2006). FSA also extends credit assistance to deserving socially disadvantaged borrowers whose access to regular farm loans could be constrained by racial, ethnic, or gender considerations (Ahrendsen et al, 2005).…”
mentioning
confidence: 99%
“…Authorities were added in the 1970s to finance selected rural infrastructure such as housing, water supply, and waste disposal, as well as rural business and industrial development (Brake and Melchar 1970, p. 455). More recently these programs have been administered by the Farm Services Agency (FSA), with increased emphasis on guaranteed rather than direct loans and loans to beginning and socially disadvantaged farmers (Ahrendsen et al 2005).…”
Section: Contribution #2: Agricultural Economists Have Played a Key Rmentioning
confidence: 99%